Key technology research for mobile police terminal fingerprint collection for quick comparison using automated fingerprint identification system - Shengjun Sun; Yaomin Gu; Lan Wang; Ping Gu; Yuankai Li (Wolters Kluwer Medknow Publications, 2019)
When the face of the inspected person and the photograph on their identification (ID) card cannot be clearly matched, the individual is undocumented, or the ID is forged, it is often difficult for the on-site police to respond in time. This study proposes a number of key technologies for collecting fingerprints at mobile terminals for fast comparison using an automated fingerprint ID system (AFIS). These technologies ensure intelligent mobile fingerprint collection and allow the transmission of fingerprint information from the terminal to AFIS, over a wireless public security network for real-time fingerprint comparison. This study also analyzes the feasibility and effectiveness of the proposed technologies for system design and the applicability of fingerprint ID algorithms. The system achieved good results in a test by the Shanghai Public Security Bureau Criminal Investigation Corps.